Pennak´s Freshwater invertebrates of the United States: Porifera to Crustacea - Grant Smith, Douglas (Jonh Wiley & Sons / New York, 2001)
Pennak's Freshwater Invertebrates of the United States, is the thorough knowledge of aquatic invertebrates that is essential to understanding the community structure of freshwater environments: Magnitude of the Freshwater Environment, The Chemical Divergence, Origins of the Freshwater Fauna. Freshwater Emigrants to the Sea. Major Distinctions Between Marine and Freshwater Invertebrates. Evolutionary Shortcomings in Freshwaters. Atypical Freshwater Habitats. Dispersal and Barriers. The Epidemic of Exotics. Food Webs. Collecting Ethics. Comment Porifera. Cnidaria. Platyhelminthes. Nemertea. Gastrotricha. Rotifera. Nematoda. Nematomorpha. Tardigrada. Entoprocta. Ectoprocta. Annelida. Mollusca. Arachnida. Introduction to the Crustacea. Phyllopodous Branchiopoda. Cladoceran Branchiopoda. Copepoda. Branchiura. Ostracoda. Minor Malacostraca. Isopoda. Amphipoda. Decapoda.